Monte Carlo studies of critical behaviour of systems with long-range correlated disoder - Prudnikov, V.V.; Prudnikov, P.V.; Dorofeev, S.V.; Kolesnikov, V.Yu. (Condensed Matter Physics, 2005)
Monte Carlo simulations of the short-time dynamic behaviour are reported for three-dimensional Ising model and XY-model with long-range spatially correlated disorder at criticality, in the case corresponding to linear defects. The static and dynamic critical exponents are computed with the use of the corrections to scaling. The obtained values of the exponents are in a good agreement with results of the field-theoretic description of the critical behaviour of this model in the two-loop approximation and with our results of Monte Carlo simulations of three-dimensional Ising model in equilibrium state.